Zero temperature coefficient of resistance of the electrical-breakdown path in ultrathin hafnia. (29th August 2017) - Zhang, H Z; Ang, D S
Abstract: The recent widespread attention on the use of the non-volatile resistance switching property of a microscopic oxide region after electrical breakdown for memory applications has prompted basic interest in the conduction properties of the breakdown region. Here, we report an interesting crossover from a negative to a positive temperature dependence of the resistance of a breakdown region in ultrathin hafnia as the applied voltage is increased. As a consequence, a near-zero temperature coefficient of resistance is obtained at the crossover voltage. The behavior may be modeled by (1) a tunneling-limited transport involving two farthest-spaced defects along the conduction path at low voltage and (2) a subsequent transition to a scattering-limited transport after the barrier is overcome by a larger applied voltage.